Perioperative Management of a Patient with Cold Urticaria - Agbenyefia, Priscilla; Shilliam, Lance A.; Stoicea, Nicoleta; Roth, Andrew; Moran, Kenneth R. (Frontiers in Medicine, 2017)
Cold urticaria consists of an allergic immune response to cold temperatures with symptoms ranging from pruritic wheals to life-threatening angioedema, bronchospasm, or anaphylactic shock. Adequate planning to maintain normothermia peri-operatively is vital due to impaired hypothalamic thermoregulation and overall depression of sympathetic outflow during deep sedation and general anesthesia. This case report describes the successful perioperative management of a 45 year-old female with a history of cold urticaria undergoing a laparoscopic Nissen fundoplication for refractory gastroesophageal reflux disease and discusses how to appropriately optimize the care of these patients.